PENGOBATAN TRADISIONAL PUSUIK TAKINO PADA MASYARAKAT DESA TOLONG KECAMATAN LEDE KABUPATEN TALIABU UTARA MALUKU UTARA - Mansye Estefania Fatima (HOLISTIK, Journal of Social and Culture, 2023)
The system of medicine has developed rapidly in today's times and has touched almost all walks of life along with the advancement of science and technology. Likewise, traditional medicine is still alive and becomes a model of alternative medicine in society. Its implementation is also based on knowledge passed down orally and in writing. Traditional medicine is still used in people's lives even though modern medicine systems have been widely known and even applied both in urban and rural areas. As found in the Taliabu community in Tolong Village, they are familiar with the traditional medicine knowledge system that has been used by the local community for hundreds of years, namely before the entry of modern medicine, known as Pusuik Takino, Pusuik Takino traditional medicine is still practiced in the lives of people in Tolong Village even though there are medical personnel available. The desire from within humans to treat illness and maintain health triggers themselves to get treatment in order to get healing even though sometimes the treatment system that is carried out does not enter into logical or irrational thinking. The choice of treatment is because the treatment that has been done has not brought healing due to lack of medical personnel, financial conditions, thus encouraging someone to try other alternatives. Keywords: tradition, traditional medicine, pusuik takino